Increasing The Competitiveness Of Msmes In Karawang Through Digital Technology And Sustainable Business Models - Wike Pertiwi (SEAN Institute, 2024)
This study aims to analyze the level of adoption of digital technology and the Sustainable Business Model by MSMEs in Karawang, as well as identifying supporting factors, obstacles, and their impact. Qualitative and quantitative approaches are used in this study. Through online surveys and in-depth interviews, the research results show that the majority of MSMEs in Karawang have integrated digital technology, such as social media and e-commerce, with their operations. A number of MSMEs also adopt sustainable business practices, although to varying degrees. Supporting factors include training, financial support, and awareness of the benefits. Key barriers include cost and lack of understanding. The implication of this research is the need for broader training to increase MSMEs' understanding of the potential of digital technology and sustainable business practices. Financial and educational support should also be considered to overcome barriers. The importance of better internet access is also a focus in driving digital technology adoption. Overall, this research provides important insights about the adoption of digital technology and sustainable business models among MSMEs in Karawang. The implications of the results of this research can help formulate further strategies in supporting the positive growth and transformation of MSMEs in the digital era.